Fabrication of nanoemulsion loaded with cefuroxime for efficient translocation across the blood brain barrier - Harun, Siti Norhawani (2018)
Meningitis is one of the commonest and most debilitating acute neurological conditions. Drugs that are effective against diseases in the central nervous system and reach the brain via the blood compartment must pass the blood brain barrier (BBB), the unique interface that formed protection against potentially harmful molecules. Antibiotics in high doses had been used to treat this illness however, with significant increase in side effects. Nanoemulsion was an effective drug nanocarrier due to their biocompatibility, relative stability, high drug loading capacity, preserved cytotoxicity and ability to protect drugs from hydrolysis and enzymatic degradation in physiologic conditions. In this research, a nanosystem for blood-brain barrier translocation utilizing nanoemulsions loaded with cefuroxime were developed. This new form of drug delivery will be able to reduce the peripheral side effects of the cefuroxime and at the same time increase the penetration across the BBB. Optimization, characterization and stability evaluation were perfomed to ensure the formulated nanoemulsion fulfilled the requirement for parenteral drug delivery. The characterization revealed particle size of 100.32 ± 0.75 nm, polydispersity index of 0.18 ± 0.01, zeta potential of −46.9 ± 1.39 mV, viscosity of 1.24 ± 0.34 cps and osmolality of 285.33 ± 0.58 mOsm/kg, indicating the nanoemulsion compatibility for parenteral application. Cefuroxime loaded nanoemulsion (CLN) was subjected to in vitro and in vivo studies. A humanized in vitro model of blood brain barrier based on cocultures of human microvascular endothelial cells (hCMEC/D3) and normal human astrocyte (NHA) was developed. This model was validated to ensure it closely resemble the microenvironment condition of blood brain barrier. This model was used to evaluate the penetration efficiency of cefuroxime loaded nanoemulsion. The in vitro study showed that the formulated CLN has higher apparent permeability (0.04 ± 0.01 cm/h) when compared to cefuroxime solution (0.02 ± 0.02 cm/h). The pharmacokinetic profile generated from in vivo study revealed that CLN was successfully improved the plasma and brain concentration of cefuroxime when compared to cefuroxime solution. From the results obtained, drug loaded nanoemulsion could be an effective carrier for drug delivery across the brain.